Srovnání účetních a daňových aspektů zaměstnaneckých benefitů vybraných subjektů veřejné sféry - Šuralová, Adriana (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Bakalářská práce se zabývá srovnáním zaměstnaneckých benefitů. Teoretická část se zabývá významem personální práce a poskytování benefitů podle účetního a daňového hlediska dle české legislativy. Analytická část obsahuje poskytování benefitů ve vybraných subjektech veřejné sféry v Jihomoravském kraji. V návrhové části práce jsou vytvořeny návrhy na změny, které by vedly k optimalizaci nákladů.

The bachelor thesis deals with the comparison of employee benefits. The theoretical part deals with the meaning of personnel work and provision of benefits according to accounting and tax aspects according to Czech legislation. The analytical part includes the provision of benefits in selected public sector entities in the South Moravian Region. In the design part of the thesis, proposals for changes that would lead to cost optimization are made.
Comparison of Accounting and Tax aspects of Employee Benefits in Selected Public Entities
Keywords: Personalistika; motivace; odměňování; hodnocení; zaměstnanecké benefity; účetní aspekty; daňové aspekty; Human resources; motivation; remuneration; assessment; employee benefits; accounting aspects; tax aspects